2023
DOI: 10.3389/fneur.2022.958166
|View full text |Cite
|
Sign up to set email alerts
|

Daily blood pressure variability in relation to neurological functional outcomes after acute ischemic stroke

Abstract: BackgroundPrior research has shown inconclusive findings regarding the relationship between blood pressure variability (BPV) in acute ischemic stroke (AIS) and functional outcomes. Most research has examined the connection between short-term BPV during the early 24–72 h after the occurrence of ischemic stroke and functional prognosis. We sought to determine the relationship between daily BPV at 7 days of commencement and functional outcomes during the 3 months following AIS.MethodsAltogether, 633 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In patients with higher SBPV, we found that RIC significantly improved the functional outcomes compared with usual care alone, suggesting the significant effect of SBPV on RIC efficacy. Previous studies demonstrated that high SBPV was associated with poor functional outcome after acute ischemic stroke 11 , 16 . After acute moderate ischemic stroke, the cerebral autoregulation was impaired 17 .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In patients with higher SBPV, we found that RIC significantly improved the functional outcomes compared with usual care alone, suggesting the significant effect of SBPV on RIC efficacy. Previous studies demonstrated that high SBPV was associated with poor functional outcome after acute ischemic stroke 11 , 16 . After acute moderate ischemic stroke, the cerebral autoregulation was impaired 17 .…”
Section: Discussionmentioning
confidence: 94%
“…In the current study, we found that higher SBPV was associated with more benefit from RIC treatment, while 2-week RIC treatment had no effect SBPV after acute ischemic stroke. SBPV was previously reported to be associated with poor outcome after acute ischemic stroke 11 , 16 . Considering the neutral effect of RIC treatment on SBPV and more benefit from RIC treatment in patients with higher SBPV, we inferred the efficacy of RIC treatment in stroke distinguished by SBPV may be attributed to the influence of SBPV on cerebral perfusion rather than the influence of RIC on SBPV.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations